Report on the Third Seminar on Islamic Economics: Resource Mobilization and Investment in an Islamic Framework The Catholic University of America, Washington, D.C. Herefeld Auduorium, Hannan Hall Jumada al Akhirah 4-5, 1411 December 22-23, 1990 (American Journal of Islam and Society, 1991)
The Third Seminar on Islamic Economics, held under the sponsorshipof the International Institute of Islamic Thought (IIIT) and the Associationof Muslim Social Scientists (AMSS), took on an international character withdelegates in attendance from as far east as Malaysia, Egypt, and Saudi Arabiain addition to participants from Canada and the United States. This year'stheme for the conference, "Resource Mobilization and Investment in an IslamicFramework;' evoked considerable interest among both academicians andpractitioners of the Islamic economic reform movement. Evidence of thisinterest was seen in the large number of research papers received on thesubject although, regrettably, funding limitations prevented many a scholarfrom participating in the meetings.The first day's sessions opened with brief remarks from Sayyid M. Syeed,general secretary of the AMSS, and Zaidi Sattar, program director for theseminar. Their remarks, while highlighting the significant strides made inthe past decade in research on Islamic economics, pointed to the substantialfinancial and logistical constraints that remain in the advancement of futureresearch in the area. IIIT and AMSS were commended for their past rolein this endeavor, and hopes were expressed for a more vigorous role in thefuture.The highlight of the opening session was the thoughtful inaugural addressby Taha Jabir al ‘Alwani, President, IIIT, who emphasized the importanceof the “human” element in the organization and management of economicresources as “. . . man is both intellect ready for thought, and hands readyfor action.” Citing from the Holy Qur’an and the works of Islamic scholars,he stressed that Islamic thought has much to offer in the emancipation ofthe ummah from the debilitating influence of colonialism. Development ofthe mind, he argued, is as critical to a society’s growth process as is thedevelopment of economic resources ...